2022
DOI: 10.1002/ece3.9593
|View full text |Cite
|
Sign up to set email alerts
|

Real‐life research projects improve student engagement and provide reliable data for academics

Abstract: Student engagement can have a positive influence on student success. Many methods exist for fostering engagement but tend to be generic and require tailoring to specific contexts, subjects, and students. In the case of undergraduate science students, practical classes are a popular tool for increasing engagement. However, despite strong potential for improvement via links with “real life” research projects (RLRPs), few academic staff incorporate research participation with teaching activities. This is potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…A similar study involved senior and graduate students to detect land use changes via Landsat 8 imagery yielded in precise land use change detection in Texas [39]. The scientific data provided by these CUREs has been evaluated to be reliable and of sufficient quality for research use, especially when compared to data collected by a non-experimental (i.e., not in a CURE) group [40], which supports an ideology for the increased inclusion of CUREs to contribute to large environmental investigations. Research groups may use such databases in confidence, and in turn, the students gain new skills through working on an original research topic that can pique their interest in similar fields.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study involved senior and graduate students to detect land use changes via Landsat 8 imagery yielded in precise land use change detection in Texas [39]. The scientific data provided by these CUREs has been evaluated to be reliable and of sufficient quality for research use, especially when compared to data collected by a non-experimental (i.e., not in a CURE) group [40], which supports an ideology for the increased inclusion of CUREs to contribute to large environmental investigations. Research groups may use such databases in confidence, and in turn, the students gain new skills through working on an original research topic that can pique their interest in similar fields.…”
Section: Discussionmentioning
confidence: 99%
“…Among the myriad subjects that constitute the curriculum, Research Methodology (RM) emerges as both vital and challenging. It not only equips students with the ability to decipher and design intricate research patterns but also nurtures a critical and analytical mindset crucial for academic and professional success [1,2] .…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that classes that incorporate real-world practical experience. [5,6], especially in a collaborative project [7], help students immensely in their later career path, and eventually contribute to society's general development.…”
Section: Introductionmentioning
confidence: 99%